TANGGAPAN MAHASISWA DALAM PEMBELAJARAN ANATOMI MANUSIA BERBANTUKAN APLIKASI AUGMENTED REALITY - Kusmawati, Wiwik; Kurniawan, Choirul; Tobing, Sari Mellina (BIOPENDIX: Jurnal Biologi, Pendidikan dan Terapan, 2022)
Background: Augmented Reality has great potential in education, and more amazingly, it opensup new fields and creates different kinds of learning.Methods: The research method used is descriptive qualitative through survey methods. Theinstrument used is a questionnaire.Results: Based on the results of a questionnaire survey of 6 question indicators, an average of81.82% was obtained in the agree category and 18.185% respondents who answered disagreed.Conclusion: The conclusion in this study is that there is a positive response from students.